Development and usability evaluation of the mobile application for patients with chronic vestibular syndrome - Cao, Xuejiao (My University, 2024)
Background and Objectives Chronic vestibular syndrome (CVS) is nonspecific and often goes untreated, which leads to disability and handicap. And recently, vestibular rehabilitation therapy (VRT) has been recommended as a first-line treatment for CVS. However, its accessibility is limited in China and many other developing countries for several reasons. Therefore, Internet-based approach may be used in situations such as long distance from the hospitals or with financial difficulty. The study had four specific aims: Part1. Determination of the App modules and functions for CVS patients and development of the App prototype. Part 2. Acquisition of user experience. Part 3. Calculation of user requirements importance and determination of optimization strategy Part 4. Usability evaluation of the App Methods In part 1, the researcher conducted two rounds of focus groups:8 specialists in the first group and 11 specialists in the second group, to explore the expected benefits and potential concerns of an App for CVS patients and determine the modules and functions of the App. In part 2, Face-to-face interviews with patients or their main caregivers were conducted in conferences. After the interview, patients were asked to fill out a general information questionnaire. Data collection and analysis were carried out simultaneously in this part. In part 3, based on the KANO model, the survey questionnaire was conducted to further analyze user requirements for App optimization. A combination of electronic and paper-based questionnaires was used. In part 4, usability was evaluated by quantitative research, using user testing and a questionnaire method. Twenty potential users were recruited in this part through the convenience sampling method Results In Part 1 of the study, 8 modules were identified, including 20 specific functions in total. Based on the results of focus groups, an App prototype was developed over six months, encompassing design and coding. In Part 2 of the study (acquisition of user experience), interview results indicated that participants expressed positive evaluations regarding the "perceived usefulness" of this App. However, in terms of usability, there were several impediments, such as the presence of over-specialized content and intricate patterns. Regarding the optimization, 7 user requirements for enhancing user-friendliness were obtained. In part 3 of the study, three optimization suggestions for better usability were finally determined, including more understandable language, adding rehabilitation exercises time-reminder, personalized font size. The post-optimized design and content have garnered recognition from specialists. In Part 4 of the study, from a holistic perspective, the App exhibited favorable usability and garnered a notably high level of user satisfaction. Conclusions This research designed and developed a mHealth App for CVS patients. Based on the KANO model, user experience and optimization requirements for the App prototype were acquired by interviews and importance of these requirements was calculated. Three optimization strategies for better usability were then determined. The usability of this App was evaluated finally and it exhibited favorable usability, garnered a notably high level of user satisfaction.

Tausta and Tavoitteet Krooninen tasapainohäiriö (CVS) on epämääräinen ja usein hoitamaton tila, mikä johtaa vammaisuuteen ja haittaan. Viime aikoina tasapainoelinten kuntoutushoito (VRT) on suositeltu ensisijaiseksi hoidoksi CVS:lle. Kuitenkin sen saatavuus on rajoitettua Kiinassa ja monissa muissa kehitysmaissa useista syistä. Siksi internet-pohjaista lähestymistapaa voidaan käyttää tilanteissa, kuten pitkien etäisyyksien takia sairaaloihin tai taloudellisen vaikeuden vuoksi. Tämän tutkimuksen tavoitteena oli suunnitella ja kehittää mHealth-sovellus CVSpotilaille ja varmistaa sen käytettävyys. Metodit Tutkimus koostui neljästä osasta: 1) Sovellusmoduulien ja -toimintojen määrittäminen CVSpotilaille ja sovelluksen prototyypin kehittäminen; 2) Käyttäjäkokemuksen hankkiminen; 3) Käyttäjävaatimusten tärkeyden laskeminen ja optimointistrategian määrittäminen; 4) Sovelluksen käytettävyyden arviointi. Tulokset Osa 1: Sovellusmoduulit ja -toiminnot CVS-potilaille ja sovellusprototyypin kehittäminen. Lopulta tunnistettiin 8 moduulia, jotka sisälsivät yhteensä 20 tarkkaa toimintoa. Osa 2: Käyttäjäkokemuksen hankkiminen. Haastattelutulosten perusteella osallistujat ilmaisivat positiivisia arvioita tämän sovelluksen "koetusta hyödyllisyydestä". Kuitenkin käytettävyyden osalta oli useita esteitä, kuten liian erikoistunut sisältö ja monimutkaiset mallit. Optimoinnin osalta saatiin 7 käyttäjän vaatimusta käyttäjäystävällisyyden parantamiseksi. Osa 3: Käyttäjävaatimusten tärkeyden laskeminen ja optimointistrategian määrittäminen. KANO-mallin mukaan suurin vaatimusten tärkeys oli ymmärrettävämmässä kielessä, jonka jälkeen seurasivat harjoitusten aikamuistutukset, asianmukaiset ääniohjeet ja suurempi tekstinäyttö. Edellisten haastatteluiden sisällön ja strategioiden toteuttamiskelpoisuuden perusteella kolme optimointiehdotusta paremmalle käytettävyydelle määritettiin lopulta, mukaan lukien ymmärrettävämpi kieli, harjoitusten aikamuistutuksen lisääminen, henkilökohtainen fonttikoko. Jälkikäteen optimoitu suunnittelu ja sisältö saivat tunnustusta asiantuntijoilta. Osa 4: Sovelluksen käytettävyyden arviointi. Kokonaisvaltaisesti sovellus osoitti suotuisaa käytettävyyttä ja sai huomattavan korkean käyttäjätyytyväisyystason. Johtopäätökset Tämä tutkimus suunnitteli ja kehitti mHealth-sovelluksen CVS-potilaille. KANO-mallin perusteella käyttäjäkokemus ja optimointivaatimukset sovellusprototyypille hankittiin haastatteluilla ja näiden vaatimusten tärkeys laskettiin. Kolme optimointistrategiaa paremmalle käytettävyydelle määritettiin sen jälkeen. Lopuksi tämän sovelluksen käytettävyys arvioitiin, ja se osoitti suotuisaa käytettävyyttä ja sai huomattavan korkean käyttäjätyytyväisyystason.
Keywords: Chronic Vestibular Syndrome, Vestibular Rehabilitation, Mobile Health Application, KANO Model, Usability Evaluation, krooninen vestibulaarinen oireyhtymä, vestibulaarinen kuntoutus, mobiilisovellus terveydenhuollossa, KANO-malli, käytettävyystutkimus